2019
DOI: 10.3389/fmats.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Studies About the Hydration of Hybrid “Alkaline-Belite” Cement

Abstract: The mechanical performance of a hybrid cement containing 48% fly ash, 48% mineralized belite clinker, 1. 5% gypsum and 2.5% Na 2 SO 4 was analyzed and the hydration products were identified. The findings showed that the newly designed cement met European standard EN 197-1 compositional, mechanical and setting time requirements (cement type IVB). The hydration products forming in this blended "alkaline-belite" cement (as it was determined through XRD, 29 Si and 27 Al MAS NMR and electron microscopy) consisted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Table 4 shows a high percentage of Al 2 O 3 and ratios of CaO/SiO 2 = 3.07 and Al 2 O 3 /SiO 2 = 2.54, indicating the formation of the C-A-S-H gel [99]. Formation of the C-A-S-H gel was also reported by Martin and Sánchez-Herrero in their studies focusing on the CSA-FA blends [28,114]. The microstructure of the sample containing CSA, VA, and SCGs is shown in Figure 9c.…”
Section: Scanning Electron Microscopy and Energy Dispersive Electron ...supporting
confidence: 69%
See 1 more Smart Citation
“…Table 4 shows a high percentage of Al 2 O 3 and ratios of CaO/SiO 2 = 3.07 and Al 2 O 3 /SiO 2 = 2.54, indicating the formation of the C-A-S-H gel [99]. Formation of the C-A-S-H gel was also reported by Martin and Sánchez-Herrero in their studies focusing on the CSA-FA blends [28,114]. The microstructure of the sample containing CSA, VA, and SCGs is shown in Figure 9c.…”
Section: Scanning Electron Microscopy and Energy Dispersive Electron ...supporting
confidence: 69%
“…The image shows unreacted spherical particles of the morphology typical for FA, and the irregular shapes belong to the SCGs and CSA. The region near the cenospheres of the FA showed a high amount of CaO and Al 2 O 3 , which was associated with the C-A-S-H gel [ 79 , 114 , 115 ]. Table 4 shows a high percentage of Al 2 O 3 and ratios of CaO/SiO 2 = 3.07 and Al 2 O 3 /SiO 2 = 2.54, indicating the formation of the C-A-S-H gel [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…In studies of supplementary cementitious materials (SCMs), researchers have observed the simultaneous formation of N-(C)-A-S-H, C-(N)-A-S-H, and C-A-S-H gels within the cementitious matrix. The specific types and amounts of precursors used contribute to the presence of these different gel formations [27,32,41,42].…”
Section: Introductionmentioning
confidence: 99%